2011
DOI: 10.1007/s13139-011-0104-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Three-Phase Bone Scan for Complex Regional Pain Syndrome Type 1 with Optimally Modified Image Criteria

Abstract: Purpose Although the three-phase bone scan (TBPS) is one of the widely used imaging studies for diagnosing complex regional pain syndrome type I (CRPS-1), there is some controversy regarding the TPBS image criteria for CRPS-1.In this study, we modified the image criteria using image pattern and quantitative analysis in the patients diagnosed using the most recent consensus clinical diagnostic criteria. Materials and MethodsThe study included 140 patients with suspected CRPS-1 (CRPS-1, n=79; non-CRPS, n=61; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…In studies on diagnostic accuracy of BS the study design was prospective in seven studies [ 29 34 ] retrospective in 13 studies, [ 35 – 45 ] and mixed prospective and retrospective in one study. [ 46 ] The sample size ranged from 13 to 145 patients ( Table 1 ), mean age from 35 to 63 years, and the average disease duration from 6 to 103 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In studies on diagnostic accuracy of BS the study design was prospective in seven studies [ 29 34 ] retrospective in 13 studies, [ 35 – 45 ] and mixed prospective and retrospective in one study. [ 46 ] The sample size ranged from 13 to 145 patients ( Table 1 ), mean age from 35 to 63 years, and the average disease duration from 6 to 103 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…44,45 Recently, the Budapest criteria were developed to aid in the standardization of the diagnosis of CRPS (►Table 2). 46 Three-phase bone scan and digital infrared thermal imaging can be used as supportive 47,48 Wüppenhorst et al reported that the sensitivity and specificity of three-phase bone scan for diagnosing CRPS were 31 to 50% and 83 to 100%, respectively. 49 Thus far, no studies on the sensitivity and specificity in digital infrared thermal imaging have been conducted.…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Diagnostic performance of TPBS in CRPS ranged widely as a sensitivity between 14% and 100% and a specificity between 50% and 100% [ 39 ]. Ringer et al [ 40 ] showed the pooled sensitivity of 87% and the pooled specificity of 69% in a meta-analysis.…”
Section: Main Bodymentioning
confidence: 99%
“…However, including decreased uptake on a delayed image as a positive finding of CRPS is controversial. Decreased uptake on a delayed image might be a supportive finding for CRPS [ 39 ], however, it could be caused by disuse of affected limb [ 46 ].…”
Section: Main Bodymentioning
confidence: 99%